Zorin na obisku pri Juliji - Smolej, Tone (Primerjalna književnost, 2011)
This article studies the extent to which Josip Stritar was familiar with Rousseau and especially with his novel Julie, or the New Héloise. Part of it also focuses on Stritar's literary tourism in Montmorency.
Keywords: Stritar, Josip, 1836-1923; Rousseau, Jean-Jacques, 1712-1778; Slovene literature; slovenska književnost; francoska književnost; French literature; romani v pismih; literarni vplivi